Whole-Transcriptome Analysis Unveils the Synchronized Activities of Genes for Fructans in Developing Tubers of the Jerusalem Artichoke - Bizzarri, Marco; Delledonne, Massimo; Ferrarini, Alberto; Tononi, Paola; Zago, Elisa; Vittori, Doriano; Damiani, Francesco; Paolocci, Francesco (Frontiers in Plant Science, 2020)
Helianthus tuberosus L., known as the Jerusalem Artichoke, is a hexaploid plant species, adapted to low nutrient soils, that accumulates high levels of inulin in its tubers. Inulin is a fructose-based polysaccharide used either as dietary fiber or for the production of bioethanol. Key enzymes involved in inulin biosynthesis are well known. However, the gene networks underpinning tuber development and inulin accumulation in H. tuberous remain elusive. To fill this gap, we selected 6,365 ESTs from a H. tuberosus library to set up a microarray platform and record their expression across three tuber developmental stages, when rhizomes start enlarging (T0), at maximum tuber elongation rate (T3) and at tuber physiological maturity (Tm), in “VR” and “K8-HS142”clones. The former was selected as an early tuberizing, the latter as a late-tuberizing clone. We quantified inulin and starch levels, and qRT-PCR confirmed the expression of critical genes accounting for inulin biosynthesis. The microarray analysis revealed that the differences in morphological and physiological traits between tubers of the two clones are genetically determined since T0 and that is relatively low the number of differentially expressed ESTs across the stages shared between the clones (93). The expression of ESTs for sucrose:sucrose 1-fructosyltransferase (1-SST) and fructan:fructan 1-fructosyltransferase (1-FFT), the two critical genes for fructans polymerization, resulted to be temporarily synchronized and mirror the progress of inulin accumulation and stretching. The expression of ESTs for starch biosynthesis was insignificant throughout the developmental stages of the clones in line with the negligible level of starch into their mature tubers, where inulin was the dominant polysaccharide. Overall, our study disclosed candidate genes underpinning the development and storage of carbohydrates in the tubers of two H. tuberosus clones. A model according to which the steady-state levels of 1-SST and 1-FFT transcripts are developmentally controlled and might represent a limiting factor for inulin accumulation has been provided. Our finding may have significant repercussions for breeding clones with improved levels of inulin for food and chemical industry.